The generic drug user fee amendments: an economic perspective. Issue 1 (11th April 2018) - Berndt, Ernst R; Conti, Rena M; Murphy, Stephen J
Abstract: Since the vast majority of prescription drugs consumed by Americans are off patent ('generic'), their regulation and supply is of wide interest. We describe events leading up to the US Congress's 2012 passage of the Generic Drug User Fee Amendments (GDUFA I) as part of the Food and Drug Administration Safety and Innovation Act (FDASIA). Under GDUFA I, generic manufacturers agreed to pay approximately $300 million in fees each year of the five-year program. In exchange, the US Food and Drug Administration (FDA) committed to performance goals. We describe GDUFA I's FDA commitments, provisions, goals, and annual fee structure and compare it to that entailed in the authorization and implementation of GDUFA II on October 1, 2017. We explain how user fees required under GDUFA I erected barriers to entry and created scale and scope economies for incumbent manufacturers. Congress changed user fees under GDUFA II in part to lessen these incentives. In order to initiate and sustain user fees under GDUFA legislation, FDA requires the submission of self-reported data on generic manufacturers including domestic and foreign facilities. These data are public and our examination of them provides an unprecedented window into the recent organization of generic drug manufacturers supplying the US market. Our results suggest that generic drug manufacturing is increasingly concentrated and foreign. We discuss the implications of this observed market structure for GDUFA II's implementation among other outcomes.